2021
DOI: 10.1007/s11418-021-01571-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gentiopicroside on activation of NLRP3 inflammasome in acute gouty arthritis mice induced by MSU

Abstract: Acute gouty arthritis is a self-limiting inflammatory disease resulting from the deposition of monosodium urate (MSU) crystals. It has been shown that Gentiopicroside (GPS) possesses anti-inflammatory and analgesic functions. The aim of this study was to parse out whether GPS has an effect on acute gouty arthritis. We established an acute gouty arthritis model by the injection of MSU into the paw, and found that GPS relieves MSU-induced mechanical, thermal hyperalgesia, and paw swelling. Furthermore, GPS down-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Although NSAIDs are commonly used to treat OA, they only provide temporary relief from clinical symptoms and can cause significant side effects in the cardiovascular system, cerebrovascular system, and gastrointestinal tract [ 32 ]. Recently, there has been extensive interest in the use of GPS for the treatment of bone and joint diseases due to its potent anti-inflammatory and analgesic properties [ 19 , 33 , 34 ]. Our study revealed that the use of GPS effectively inhibited the inflammatory response in chondrocytes induced by LPS and alleviated hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Although NSAIDs are commonly used to treat OA, they only provide temporary relief from clinical symptoms and can cause significant side effects in the cardiovascular system, cerebrovascular system, and gastrointestinal tract [ 32 ]. Recently, there has been extensive interest in the use of GPS for the treatment of bone and joint diseases due to its potent anti-inflammatory and analgesic properties [ 19 , 33 , 34 ]. Our study revealed that the use of GPS effectively inhibited the inflammatory response in chondrocytes induced by LPS and alleviated hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GPS could suppress pro-infammatory cytokines release, neutrophil infiltration and NLRP3 inflammasome activation. Therefore, the effect of GPS on GA might be ascribed to the inhibition on NLRP3 infammasome ( 80 ). In another original study, the cell viability of THP-1 cells stimulated by LPS and MSU was observed to be significantly improved by epicatechin (EC) in a dose-dependent manner.…”
Section: Therapeutic Strategies For Targeting Nlrp3 In Gamentioning
confidence: 99%
“…GPS can inhibit the activation of NLRP3 inflammasomes in macrophages under in vitro conditions. GPS can be used to treat gouty arthritis by hindering the activation of the NLRP3 inflammasome [116].…”
Section: Glycosidesmentioning
confidence: 99%